Export costs and geographic diversification: Does experience matter? - Tomás Castagnino (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2010)
What drives firms' geographic diversification in international markets? I build a model to show that if some export costs are sunk and shared between alike destinations, the decision of a firm to enter a market is a function of its experience in a similar one. Using a rich firm-level dataset for Argentina I test this prediction and I provide evidence on the role and nature of shared export costs. Product adaptation costs, associated to market similarities in geography and culture, and quality upgrading costs, associated to market similarities in income level, are found to be significant. Finally, I show that the failure to consider firms' idiosyncratic experience in international markets leads to an underestimation of the difficulty to enter export markets.
Keywords: F10; F12; F13; F14; 330; firm-level; export costs; quality; experience; geographic diversification